Pendampingan Guru TK dalam Pengembangan Metode Pembelajaran Anak Usia Dini - Hunainah, Hunainah (THUFULA, 2019)
MENTORING KINDERGARDEN TEACHER IN DEVELOPMENT EARLY AGE LEARNING METHODS. This study aims to determine the ability of teachers in  preparing Weekly Working Plan  and Daily Working Plan; Applying early childhood learning methods; Making learning properties from natural materials; and the understanding of Islamic teachings based on the Holy Qur'an and Sunnah to the Kindergarten Teachers' Aisyiyah Bustanul Athfal Puloampel in 2017. In this study, the researcher used qualitative research method. Qualitative research intends to understand the phenomenon of what by research subjects such as behavior, perception, motivation, action, and others. The results showed that the teacher’s skill in using early childhood learning methods in teaching at a Kindergarten  Aisyiyah Bustanul Athfal Puloampel in 2017 is quite varios, they used lecturing method, question-answer, singing and assignment methods. This is shown by the teachers who only used student exercise books and magazines as the main learning media. The understanding of Islamic Teaching of the teacher was still minimum. This is indicated by the practice of worship of the teachers were not based on  the Decision of Tarjih Muhammadiyah.